2010
DOI: 10.5194/acp-10-39-2010
|View full text |Cite
|
Sign up to set email alerts
|

Data assimilation of CALIPSO aerosol observations

Abstract: Abstract.We have developed an advanced data assimilation system for a global aerosol model with a four-dimensional ensemble Kalman filter in which the Level 1B data from the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) were successfully assimilated for the first time, to the best of the authors' knowledge. A onemonth data assimilation cycle experiment for dust, sulfate, and sea-salt aerosols was performed in May 2007. The results were validated via two independent observations: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
193
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(196 citation statements)
references
References 36 publications
2
193
0
1
Order By: Relevance
“…In particular, studies have shown notable improvements in aerosol forecasting through the assimilation of satellite aerosol products, mostly from daytime observations (e.g., Zhang et al, 2008aZhang et al, , 2011Zhang et al, , 2014Yumimoto et al, 2008;Uno et al, 2008;Benedetti et al, 2009;Schutgens et al, 2010;Sekiyama et al, 2010). To capture the diurnal cycle, the aerosol modeling community requires nighttime satellite aerosol data hav-ing broad spatial coverage and high temporal resolution to further advance aerosol, visibility, and air quality forecasts (e.g., Zhang et al, 2011Zhang et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies have shown notable improvements in aerosol forecasting through the assimilation of satellite aerosol products, mostly from daytime observations (e.g., Zhang et al, 2008aZhang et al, , 2011Zhang et al, , 2014Yumimoto et al, 2008;Uno et al, 2008;Benedetti et al, 2009;Schutgens et al, 2010;Sekiyama et al, 2010). To capture the diurnal cycle, the aerosol modeling community requires nighttime satellite aerosol data hav-ing broad spatial coverage and high temporal resolution to further advance aerosol, visibility, and air quality forecasts (e.g., Zhang et al, 2011Zhang et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in aerosol climate studies (e.g., Kaufman et al, 2002;Zhang et al, 2005a, b) and aerosol and visibility forecasting (e.g., Zhang et al, 2008aZhang et al, , 2011Benedetti et al, 2009;Sekiyama et al, 2010) have responded to the growing demand for nighttime aerosol retrievals from satellite observations. For example, by using multisensor aerosol products from the Moderate Resolution Imaging Spectroradiometer (MODIS), the Multi-angle Imaging Spectroradiometer (MISR), and the Cloud Aerosol Lidar with Orthogonal Polarization (CALIOP), Zhang et al (2011) show improvements in aerosol forecasts using combined 2-D/3-D VAR aerosol assimilation.…”
Section: Introductionmentioning
confidence: 99%
“…Then the accuracy of calculated concentration of dust is the key factor. Recently data assimilation technique is combined with CTM, and lidar data can be included in this system [3,4]. Thus, dust extinction estimated by the lidar network will raise the reliability of concentration predicted by CTM, and such results are the most suitable for epidemiology.…”
Section: Plans For Obtaining More Useful Datamentioning
confidence: 99%